Inside the Workplace: Findings from the 2004 Workplace Employment Relations Survey - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "Inside the Workplace: Findings from the 2004 Workplace Employment Relations Survey," by Barbara Kersley, Carmen Alpin, John Forth, Alex Bryson, Helen Bewley, Gill Dix and Sarah Oxenbridge.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; Polls & surveys; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work environment